Submillimeter Diameter Poly(Vinyl Alcohol) Vascular Graft Patency in Rabbit Model - Cutiongco, Marie F. A.; Kukumberg, Marek; Peneyra, Jonnathan L.; Yeo, Matthew S.; Yao, Jia Y.; Rufaihah, Abdul Jalil; Le Visage, Catherine; Ho, Jackie Pei; Yim, Evelyn K. F. (Frontiers in Bioengineering and Biotechnology, 2016)
Microvascular surgery is becoming a prevalent surgical practice. Replantation surgeries, hand reconstruction, orthopedic and free tissue transfer procedures all rely on microvascular surgery for the repair of venous and arterial defects at the millimeter and sub-millimeter levels. Often, a vascular graft is required for the procedure as a means to bridge the gap between native arteries. While autologous vessels are desired for their bioactivity and non-thrombogenicity, the tedious harvest process, lack of availability and caliber or mechanical mismatch contribute to graft failure. Thus, there is a need for an off-the-shelf artificial vascular graft that has low thrombogenic properties and mechanical properties matching those of sub-millimeter vessels. Poly(vinyl alcohol) hydrogel (PVA) has excellent prospects as a vascular graft due to its bioinertness, low thrombogenicity, high water content and tunable mechanical properties. Here, we fabricated PVA grafts with sub-millimeter diameter and mechanical properties that closely approximated those of the rabbit femoral artery. In vitro platelet adhesion and microparticle release assay verified the low thrombogenicity of PVA. A stringent proof of concept in vivo test was performed by implanting PVA grafts in rabbit femoral artery with multi-level arterial occlusion. Laser Doppler measurements indicated the improved perfusion of the distal limb after implantation of the PVA grafts. Moreover, ultrasound Doppler and angiography verified that the sub-millimeter diameter PVA vascular grafts remained patent for two weeks without the aid of anti-coagulant or anti-thrombotics. Endothelial cells were observed in the luminal surface of one patent PVA graft. The advantageous non-thrombogenic and tunable mechanical properties of PVA that are retained even in sub-millimeter diameter dimensions support the application of this biomaterial for vascular replacement in microvascular surgery.